2007
DOI: 10.1158/1055-9965.epi-06-0694
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Hypermethylation of Tumor Suppressor Genes in Urine from Patients with Cervical Neoplasia

Abstract: We examined the feasibility of using detection of high-risk human papillomavirus (HPV) DNA in combination with the presence of aberrantly methylated genes (DAPK1, RARB, TWIST1, and CDH13 ) for urine-based cervical cancer screening. Urine samples from 129 Senegalese women, aged 35 years or older, 110 with (same day) biopsy-proven cervical neoplasia [cervical intraepithelial neoplasia grade 1 (CIN-1): n = 9; CIN-2 -3/carcinoma in situ (CIS): n = 29; invasive cervical cancer (ICC): n = 72], and 19 without cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 59 publications
0
27
0
1
Order By: Relevance
“…Specimen collection should ideally be non-invasive and easily repeatable for monitoring residual or recurrent cancer after treatment. Since hypermethylated DNA may serve as a potential molecular tumor marker due to its high specificity in differentiating cancer from normal tissues, detection of aberrant methylation of tumor suppressor genes in the bodily fluids of cancer patients is attracting increasing attention, for example, in the detection of prostate and cervical cancer from urine, head and neck squamous cell carcinoma by saliva, lung cancer by sputum and bronchial lavage, ovarian cancer by peritoneal fluid, and nasopharyngeal carcinoma by mouth and throat fluid, or nasopharyngeal swab and plasma/serum or blood cells from peripheral blood [22-28]. Among these sample types, the most simple and broadly applicable strategy is to obtain peripheral blood samples from patients.…”
Section: Discussionmentioning
confidence: 99%
“…Specimen collection should ideally be non-invasive and easily repeatable for monitoring residual or recurrent cancer after treatment. Since hypermethylated DNA may serve as a potential molecular tumor marker due to its high specificity in differentiating cancer from normal tissues, detection of aberrant methylation of tumor suppressor genes in the bodily fluids of cancer patients is attracting increasing attention, for example, in the detection of prostate and cervical cancer from urine, head and neck squamous cell carcinoma by saliva, lung cancer by sputum and bronchial lavage, ovarian cancer by peritoneal fluid, and nasopharyngeal carcinoma by mouth and throat fluid, or nasopharyngeal swab and plasma/serum or blood cells from peripheral blood [22-28]. Among these sample types, the most simple and broadly applicable strategy is to obtain peripheral blood samples from patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although frequency of urine HPV detection increased with increasing severity of the lesion, it was consistently less as compared with that in cervical specimen for each grade of lesion. Feng et al (2007) also demonstrated greater positivity for HPV-DNA in urine samples from patients of invasive cervical cancer (70%), HSIL (59%) and LSIL (44%) as compared with those with no cytological abnormalities (11%). Daponte et al (2006) collected paired samples from 100 consecutive women with abnormal cytology attending the colposcopy clinic.…”
Section: Comparative Detection Of Squamous Intraepithelial Lesionsmentioning
confidence: 92%
“…One study by Feng et. al [35] examined the usage of three methylation biomarkers (DAPK1, RARB, CDH13, and TWIST1) in Senegal, a low-resource setting. These researchers examined the feasibility of using these markers for a urine based cervical cancer screening method.…”
Section: Screening Strategies Identifying Epigenetic Changesmentioning
confidence: 99%